1991
DOI: 10.1148/radiology.181.3.1947076
|View full text |Cite
|
Sign up to set email alerts
|

Venous thrombosis in patients who have undergone major hip or knee surgery: detection with compression US and impedance plethysmography.

Abstract: To compare the sensitivity, specificity, and predictive values of compression ultrasonography (US) in postoperative orthopedic patients with those of (a) impedance plethysmography in postoperative patients and (b) compression US in symptomatic outpatients, the authors performed an investigator-blinded cohort study. One hundred thirty-four consecutive inpatients who had undergone elective knee-replacement surgery or surgery for a fractured hip and 65 consecutive outpatients with clinically suspected venous thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 0 publications
1
31
0
2
Order By: Relevance
“…Un ejemplo es el caso de la ecografía doppler de extremidades inferiores para el diagnóstico de trombosis venosa profunda (TVP), donde la exactitud del test para el diagnóstico de TVP proximal es mayor en pacientes ambulatorios sintomáticos que en pacientes postoperatorios asintomáticos 6 . en general, en los pacientes…”
Section: ¿Son Aplicables a Mis Pacientes Los Resultados Del Estudio?unclassified
See 1 more Smart Citation
“…Un ejemplo es el caso de la ecografía doppler de extremidades inferiores para el diagnóstico de trombosis venosa profunda (TVP), donde la exactitud del test para el diagnóstico de TVP proximal es mayor en pacientes ambulatorios sintomáticos que en pacientes postoperatorios asintomáticos 6 . en general, en los pacientes…”
Section: ¿Son Aplicables a Mis Pacientes Los Resultados Del Estudio?unclassified
“…Un ejemplo es el caso de la ecografía doppler de extremidades inferiores para el diagnóstico de trombosis venosa profunda (TVP), donde la exactitud del test para el diagnóstico de TVP proximal es mayor en pacientes ambulatorios sintomáticos que en pacientes postoperatorios asintomáticos 6 . en general, en los pacientes con expresión clara de la enfermedad (ya sea por mayor severidad o tiempo de evolución), el likelihood ratio (lr) se aleja más de 1. en cambio en pacientes menos afectados por la condición en estudio (estadíos precoces o expresión leve), el lr se acerca al valor 1, es decir, el test tiene menor utilidad.…”
Section: ¿Son Aplicables a Mis Pacientes Los Resultados Del Estudio?unclassified
“…data] and very poor for calf DVT (overall sensitivity 16%) [18][19][20] (table 5). Conventional duplex for femoropopliteal segment DVT was better with an overall sen sitivity of 91 % and specificity of 98% [21 -25] (table 6).…”
Section: Results From Post-operative Surveillance Studiesmentioning
confidence: 99%
“…Studies in symptomatic patients have consistently shown a high sensitivity and specificity (97% and 97%) for proximal deep venous thrombosis. [17][18][19] Conventional duplex imaging, however, has its drawbacks. Errors continue to be made in the detection of thrombi located in the calf veins and femoral adductor canal region.…”
Section: Discussionmentioning
confidence: 99%